2017
DOI: 10.1093/schbul/sbx072
|View full text |Cite
|
Sign up to set email alerts
|

Embracing Psychosis: A Cognitive Insight Intervention Improves Personal Narratives and Meaning-Making in Patients With Schizophrenia

Abstract: Schizophrenia is a complex psychiatric disorder with unknown and presumably heterogeneous etiology. While the disorder can have various outcomes, research is predominantly "deficit-oriented" emphasizing the hardship that the disorder inflicts on sufferers as well as their families and society. Beyond symptom reduction, imparting patients with hope and meaning in life is increasingly considered an important treatment target, which may raise self-esteem, and reduce self-stigma and suicidal ideation. The present … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 76 publications
2
27
0
Order By: Relevance
“…Furthermore, memory delusion distress and social quality of life were improved by MCT in patients with schizophrenia, suggesting that MCT had beneficial effects on symptomatic parameters and several cognitive functions (51). They also showed that patients with schizophrenia who received MCT exhibited a significant positive change in attitude toward their illness compared with the active control condition and enhanced meaning-making in patients (52). A systematic review showed that MCT was effective in reducing cognitive biases and delusions and improving insights and several aspects of neurocognitive functions in schizophrenia (9).…”
Section: Discussionmentioning
confidence: 95%
“…Furthermore, memory delusion distress and social quality of life were improved by MCT in patients with schizophrenia, suggesting that MCT had beneficial effects on symptomatic parameters and several cognitive functions (51). They also showed that patients with schizophrenia who received MCT exhibited a significant positive change in attitude toward their illness compared with the active control condition and enhanced meaning-making in patients (52). A systematic review showed that MCT was effective in reducing cognitive biases and delusions and improving insights and several aspects of neurocognitive functions in schizophrenia (9).…”
Section: Discussionmentioning
confidence: 95%
“…Poor insight in schizophrenia is prevalent across cultures and phases of illness (Lysaker et al 2018). A previous study reported that up to 80% of all psychotic patients do not take their medication as prescribed mainly because of poor insight, which consequently affecting their awareness about their own needs (Garcíaet al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The integrated model of insight in schizophrenia has suggested that poor insight may result from multiple factors which compromise persons' abilities to integrate streams of information into a personal awareness of psychiatric challenges, and make adaptive responses (Lysaker et al 2018). This model hypothesized that the origins of poor insight in schizophrenia may result, in part, from deficits in metacognitive capacity, or difficulties forming a complex and integrated understanding of both one's own thinking as well as the thinking of others regardless of clinical profile .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations